The impact of OECD research on the education system of Kazakhstan - Sarmurzin, Y.; Amanzhol, N.; Toleubayeva, K.; Zhunusova, M.; Amanova, A. (Asia Pacific Education Review, 2021)
In education, reform and renewal are constant. Policies are continually changing to meet the needs of the times and the society. Political advisors, such as the Organization for Economic Cooperation and Development, play an important role among private consultants as policy actors. According to Gunter's (in: Howlett and Mukerjee (eds), Handbook of policy formulation, Edward Elgar Publishers, 2017) classification of policy actors, the OECD can be classified as a supra-national organization. This paper examines the impact of OECD research on the education system of Kazakhstan. Based on the literature, the authors address two key issues-what role the OECD is performing in education policy reforms in Kazakhstan and whether this facilitates or undermines the provision of public education. The authors focus on the influence of Programme for International Student Assessment (PISA) as a global phenomenon, how Kazakhstan has embraced this international test, and how, even though PISA has made little or no difference to student outcomes, it is still credited for educational achievements.
Keywords: OECD; PISA; Kazakhstan; Policy actors; Education